SP0064 Imaging Biomarkers as A Useful Tool in Gout Disease. (10th June 2014) - Manger, B.
Abstract : Conventional radiography can show characteristic features of gouty arthritis such as intraosseous cysts or large erosions with overhanging edges in an advanced tophaceous stage. For early diagnosis, however, conventional X-rays are non-specific. Musculoskeletal ultrasound has the potential to support the non-invasive diagnosis of gouty arthritis. Sonography can detect free-floating MSU crystals in synovial fluid ("snow storm appearance") or subclinical tophaceous deposits. The most specific ultrasonographic finding, however, is the double contour sign, representing MSU deposits on the surface of hyaline cartilage (e. g. of femoral condyles or metatarsal heads). Numerous studies have demonstrated that sonography gives reproducible, sensitive, and specific results in the diagnosis of gouty arthritis. A recent study has examined, which combination of joint, cartilage, and tendon sites should be examined to get the best diagnostic information in patients with this disease. MRI is able to pick up synovitis, bone edema and erosions in gout with high sensitivity, but does not provide characteristic features to differentiate these from other forms of arthritis in early stages. Therefore, MRI does currently not offer a clear advantage to sonography in the diagnosis of gouty arthritis. Recently, yet another diagnostic method has been described, which allows non-invasive identification of sodium urate crystals deposits in the periarticular tissues. Dual energy computed tomography (DECT) is an imaging method, which uses X-ray beams of two different energies to differentiate solid sodium urate deposits from connective tissues and from calcium containing structures by their absorption properties. Several clinical studies could clearly demonstrate that DECT does not only reliably detect clinically overt tophi, but also detects subclinical urate deposition at periarticular or peritendinous sites in gout patients. Therefore, DECT may not only be a very helpful imaging method for tophus assessment and follow-up in clinical trials and during urate lowering therapy in patients with the established diagnosis of chronic gout. It may also be valuable as differential diagnostic tool in patients with "unclassified" acute or relapsing arthritides, when aspiration of synovial fluid is not possible or not successful. Disclosure of Interest: B. Manger Consultant for: Berlin-Chemie, Astra-Zeneca, Savient DOI: 10.1136/annrheumdis-2014-eular.6114